The Validity of Bilingual Teaching Material Based on STSE on Fungi Material to Practice Scientific Literacy for Senior High School Grade 10th - Dewi Purwasih; Isnawati Isnawati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
Abstract Teaching Materials are the teaching aids to explain concepts to students or evaluate their performance to increase the quality of learning, one of which is scientific literacy skills in the school. Teaching material based on STSE (science, technology, society, environment) can facilitate scientific literacy skills for students. Fungi material has to vary content related to science, technology, society, and the environment. The students can practice their scientific literacy skills. The research aimed to explain the theoretical eligibility of bilingual teaching material based on STSE on fungi material to practice scientific literacy for senior high school grade 10th. The theoretic eligibility is measured based on product validity. The research of development refers to the Model of Fenrich Instructional Development Cycle conceives phases such as analysis, planning, design, development, and implementation, in which every cycle must be evaluated and revised. The validity of the teaching material was assessed by a biology education expert, a fungi material expert, and a biology teacher of senior high school. The data were analyzed qualitatively. The developed teaching material was counted to be able to practice students' scientific literacy skills. Based on the validation result of three components are content 3.87, appearance 4, and linguistic 3.93. Based on the result of three criteria of theoretical eligibility acquired an average score of 3.93 with a percentage of 98% with a very valid category. Hence the teaching material was valid to use in the learning activity. Keywords: STSE (Science, Technology, Society, Environment), Fungi, Scientific literacy, Teaching Material